ANALISIS KEBUTUHAN LEMBAR KERJA AUDIO SISWA (LKAS) UNTUK SISWA TUNANETRA - nFn Innayah (Balai Besar Guru Penggerak Jawa Timur, 2016)
Visually impaired disabilities have requiring an appropriate medium for learning. Audio student worksheet (LKS) is one of the media for persons with disabilities are being developed. The aim of the study was to determine the subjects that require media audio LKS, format of audio LKS, player tool for audio LKS program and accompanying materials required as supporting audio LKS. This research was conducted by the method of research and development. The results of this study showed subjects that require audio LKS is a national examination subjects such as Indonesian language, English language, science and mathematics. Form of audio LKS for visually impaired disabilities is a summary with multiple choice questions. Instruments of audio LKS that suitable for visually impaired disabilities are laptop and an MP3 player. The understanding of the audio LKS for visually impaired disabilities should be complemented with an accompanying material in the form of Braille. AbstrakSiswa tunanetra membutuhkan media pembelajaran yang tepat. Lembar kerja audio siswa (LKAS) merupakan salah satu media yang dikembangkan bagi siswa tunanetra. Penelitian ini bertujuan untuk mengetahui mata pelajaran yang membutuhkan media LKAS, format LKAS, alat pemutar program untuk LKAS dan bahan penyerta yang dibutuhkan sebagai penunjang LKAS. Penelitian ini menggunakan metode penelitian dan pengembangan (R and D). Hasil penelitian mengungkapkan bahwa mata pelajaran yang membutuhkan media LKAS adalah mata pelajaran ujian nasional seperti Bahasa Indonesia, Bahasa Ingggris, IPA dan matematika. Format LKAS bagi siswa tunanetra adalah ringkasan materi dengan bentuk soal pilihan ganda. Alat pemutar program yang sesuai bagi siswa tunanetra adalah laptop dan MP3 player. Pemahaman terhadap LKAS perlu dilengkapi dengan bahan penyerta dalam bentuk Braille.